Peran Desa Adat dalam Pengelolaan Pariwisata Bahari di Desa Serangan, Denpasar, Indonesia - Ningsih, Luh Devi Charline Faradila (Journal of Tourism and Hospitality Analysis (JoTHA), 2024)
This research focuses on the role of traditional villages in managing marine tourism in Serangan Village, which is seen from the perspective of planning, organizing, mobilizing and controlling. This research used observation, interviews, surveys, documentation, and literature study for data collection techniques. The sampling technique used purposive sampling, which was distributed to 100 respondents. Data were analyzed using quantitative descriptive analysis. The results of this study indicate that the role of traditional village in the management of marine tourism in the village of Serangan is very optimal can be seen in the sub-role of the planning role has an overall average value of 4.20 (very agree / very good), the role of organizing is equal to 4.23 (very agree / very good), the role of mobilization is 4.01 (agree / good), and the role of controlling is 4.17 (agree / good).